2013
DOI: 10.1007/s12032-013-0596-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of systemic inflammatory and nutritional blood-borne markers in predicting response to neoadjuvant chemotherapy and survival in oesophagogastric cancer

Abstract: The aim of this study was to interrogate whether blood-borne inflammatory and nutritional markers predict long-term survival and response to neoadjuvant chemotherapy in radically treated oesophagogastric cancer patients. This retrospective study included 246 patients who underwent oesophageal resection for high-grade dysplasia or carcinoma between 2005 and 2010. The predictive value of routine preoperative immunonutritional blood tests was assessed for their association with survival and response to chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 73 publications
3
45
0
Order By: Relevance
“…The stage at diagnosis of EAC is the key factor in determining prognosis. The depth of invasion through the esophageal wall determines the risk of lymph node (LN) metastasis, which, in keeping with other reports, in our cohort is the most prognostic pathological finding for poor outcome [40,41]. Unfortunately, in EAC, the majority of tumors have invaded through the esophageal wall at the time of diagnosis.…”
Section: The Challenge Of Early Diagnosissupporting
confidence: 85%
See 1 more Smart Citation
“…The stage at diagnosis of EAC is the key factor in determining prognosis. The depth of invasion through the esophageal wall determines the risk of lymph node (LN) metastasis, which, in keeping with other reports, in our cohort is the most prognostic pathological finding for poor outcome [40,41]. Unfortunately, in EAC, the majority of tumors have invaded through the esophageal wall at the time of diagnosis.…”
Section: The Challenge Of Early Diagnosissupporting
confidence: 85%
“…We have proposed predictive markers of response to chemotherapy, and like many other groups have shown potential biomarkers [40]. Serum albumin was shown to be the only predictor of pathological response to chemotherapy.…”
Section: Predicting Response To Neoadjuvant Therapymentioning
confidence: 88%
“…During surgical treatment of patients with gastrointestinal tumors, the prognostic nutritional index, which is based on serum Alb and total lymphocyte count in peripheral blood, was used to assess the perioperative nutritional conditions and postoperative complications [21]. Furthermore, a study by Noble et al [22] on patients with esophagogastric cancer receiving neoadjuvant chemotherapy demonstrated that serum Alb was the only characteristic that could reliably predict pathological response to neoadjuvant chemotherapy. Although their analysis mainly included patients with adenocarcinomas, and neoadjuvant chemotherapy comprised an epirubicin-based regimen, the study suggests that malnutrition was associated with the lack of response to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…As emphasized by Noble et al, 12 additional studies would reinforce the oncological impact of PLR in oesophageal cancer. Interestingly, for palliative treatment of gastric cancer with FOLFOX regimen, normalization of PLR after one cycle of chemotherapy was associated with longer OS, with a 6 month gain from 10.9 to 16.9 months, p ¼ 0.002.…”
Section: Plr and Oesophageal Cancermentioning
confidence: 76%